Pembinaan Prestasi Olahraga Sepak Bola pada SSB Putra Mandiri di Kota Magelang Tahun 2020 - Prayoga, Hendrian; Annas, Mohamad (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the implementation of fostering soccer sports achievement at SSB Putra Mandiri. This research uses a qualitative etnographic approach. Data collection using the method of observation, interviews, and documentation. The subjects in this study were administrators, coaches, and athletes. The data analysis technique used is data triangulation technique. Data analysis with data reduction, data presentation, and drawing conclusions. The results of the research, it can be concluded that the implementation of soccer sports development in SSB Putra Mandiri is good enough, it can be seen from the aspects of pemassalan, nurseries, achievements, organizations, training programs, human resources, facilities and infrastructure as well as funding. There is no need for a dual position by the management. Optimizing sponsorship contributions for improving the welfare of SSB Putra Mandiri. The conclusion from the research is that the stages of fostering soccer sports achievements at SSB Putra Mandiri in Magelang City include the installation, nursery and achievement stages that have been going well, the management of the Putra Mandiri SSB organization has been running according to its main duties and functions and has an active role in coaching. football achievements, the training program at SSB Putra Mandiri is in good category.